PENERAPAN MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN HASIL BELAJAR PKn SISWA KELAS IV SD NEGERI 024 UPT PUNTIANAI - Matkarian '; Otang Kurniaman; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study entitled application of model contextual teaching and learning (CTL) to improve student learning outcomes civics class IV SDN 024 UPT Puntianai. This study aims to improve learning outcomes civics fourth grade students of SDN 024 UPT Puntianai. The method used is the method of classroom action research (PTK) which is implemented in the second semester of the academic year 2015/2016. The research sample is 31 students. Results of this study was obtained from the average results of study before action 61.61 increased to 15.19% with a mean cycle rata70,97 i. In the second cycle increased to 30.90% with an average of 80.65. The percentage of classical completeness of students in basic score 38.71% (not finished), increased in the first cycle to 64.52% (not finished). In the second cycle increased again to 90.32% (complete). Activities teachers in the first cycle of the first meeting obtain a percentage of 64.28% with enough categories, at a second meeting has increased with the percentage of 71.42% with both categories. Furthermore, the first meeting of the second cycle of teacher activity also increased with the percentage of 89.28% with a good category and at the second meeting of the second cycle increased again with a percentage of 96.42% with a good category. Activities of students in the first cycle of the first meeting of 67.85% with a percentage gain enough categories, at the second meeting with the percentage increased to 71.42% with enough, in this cycle the students begin to understand the learning activities with the application of ctl marked with the student's activity the first meeting of the second cycle increased with the percentage of 85.71% in both categories. At the second meeting of the second cycle increased with the percentage of 96.42% with a good category.Keywords: Contextual Teaching and Learning, learning outcomes Civics